2015
DOI: 10.3892/ijo.2015.2832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 64Cu-labeled 1,4,7-triazacyclononane, 1-glutaric acid-4,7 acetic acid (NODAGA)-galactose-bombesin analogue as a PET imaging probe in a gastrin-releasing peptide receptor-expressing prostate cancer xenograft model

Abstract: Abstract. gastrin-releasing peptide receptor (grPr) is overexpressed by a variety of human tumors and in particular, identified to be upregulated in prostate cancers. the current study aimed to develop clinically translatable BBn analogue-based radioligands for positron emission tomography (Pet) of grPr-positive tumors. We developed radiolabeled BBn analogues and modified radiolabeled galacto-BBN analogues and then investigated their tumor-targeting efficacy in vivo. the chelator 1,4,7-triazacyclononane, 1-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…In accordance with in-vivo and ex-vivo studies, significantly decreased tracer uptake of the GRPR-positive PC-3 cells was depicted in the case of the blocking experiments, whereas the blocking agent expressed no effect on control HaCaT cells. In line with our results, Kim et al reported discrete tumor uptake of [ 64 Cu]Cu-NODAGA-BBN or [ 64 Cu]Cu-NODAGA-galacto-BBN following the administration of 15 mg/BW of non-radioactive blocking ligands (NODAGA-BBN, or NODAGA-galacto-BBN) [ 37 ]. They presented the reduction of the radiopharmaceutical accumulation in the group of PC-3 tumor-bearing nude mice injected with the GRPR-blocking agent 30 min prior to the tracer administration compared to those pets that did not receive the blocking ligand [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with in-vivo and ex-vivo studies, significantly decreased tracer uptake of the GRPR-positive PC-3 cells was depicted in the case of the blocking experiments, whereas the blocking agent expressed no effect on control HaCaT cells. In line with our results, Kim et al reported discrete tumor uptake of [ 64 Cu]Cu-NODAGA-BBN or [ 64 Cu]Cu-NODAGA-galacto-BBN following the administration of 15 mg/BW of non-radioactive blocking ligands (NODAGA-BBN, or NODAGA-galacto-BBN) [ 37 ]. They presented the reduction of the radiopharmaceutical accumulation in the group of PC-3 tumor-bearing nude mice injected with the GRPR-blocking agent 30 min prior to the tracer administration compared to those pets that did not receive the blocking ligand [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…As a result, tumor uptake of [ 64 Cu]Cu-NODAGA-galacto-BBN decreased significantly in the group treated with the blocking agent (0.14 ± 0.05 %ID/g) compared with the group that did not receive the blocking agent (1.46 ± 1.20 %ID/g). 36 In this study, we acquired [ 64 Cu]Cu-NODAGA-galacto-BBN PET/CT images of mice with RIPF at 0, 2, 5, and 11 weeks after irradiating lungs with 90 Gy. When lung tissue is irradiated, inflammation is induced and mediates the progression of pulmonary fibrosis; therefore, we also acquired [ 18 F]F-FDG PET/CT images of mice with RIPF as markers for inflammation and the degree of fibrosis and compared them with GRPR-targeted imaging.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The synthesis of NODAGA-galacto-BBN(7–14)­NH 2 was conducted by FUTURECHEM (Seoul, Korea), as described in a previous study . Briefly, d -galacturonic acid was conjugated to the amine of glutamine on BBN(7–14)­NH 2 via an ester.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelators serve not only to chelate and stabilize radionuclides but also to tether them to other molecules via a chemically active functional group without causing undesirable changes in biodistribution, target binding, and pharmacokinetic. Kim et al (2015) developed clinically translatable BBN analog-based radiopharmaceuticals for the PET imaging of GRPR-overexpressed tumors. In that study, the chelator 1,4,7-triazacyclononane, 1-glutaric acid-4,7 acetic acid (NODAGA) was used to radiolabel BBN analogs and modified galacto-BBN analogs with 64 Cu.…”
Section: Bombesin and Grpr Agonistsmentioning
confidence: 99%